Resistance of acetylated Jacaranda copaia wood to termites and decaying fungi attack - BAUFLEUR,Andressa Midori Yamauchi (2022)
ABSTRACT The natural durability of the wood is essential for the definition of its use, and this property can be enhanced with the proper chemical treatment of the wood. Thus, the objective of this study was to evaluate the resistance to termites and decay fungi of Jacaranda copaia wood chemically modified through acetylation. Five experimental treatments were assessed: acetylation for 2, 4, 6 and 8 hours and a control (non-acetylated). The acetylation was carried out by immersing wood samples in acetic anhydride at 90 °C. Acetylated and control samples were subjected to the action of xylophagous termites (Nasutitermes sp.) and decaying fungi (Gloeophyllum trabeum and Trametes versicolor). The acetylation process significantly increased the resistance of Jacaranda copaia wood to the attack of the xylophagous organisms. There was no mass loss after exposure to termites of the wood in any of the acetylation treatments, while in the control wood, mass loss was 9.5%. Regarding the decaying fungi, mass loss occurred in all treatments. Acetylation for 6 and 8 hours were the most efficient chemical treatments, increasing the resistance class of the Jacaranda copaia wood to highly resistant.